Living with Seismic Phenomena in the Mediterranean and Beyond between Antiquity and the Middle Ages Proceedings of Cascia (25-26 October, 2019) and Le Mans (2-3 June, 2021) Conferences - Compatangelo-Soussignan, Rita (Archaeopress Publishing, 2022)
"In a Mediterranean area characterised by strong seismic activity, the earthquake that struck central Italy in 2016 caused considerable damage to the archaeological and historical heritage. This catastrophic event, as well as recent archaeological fieldwork and palaeoseimological research in the same area, led to the organisation in 2019 of the first International Conference Living with seismic phenomena in the Mediterranean from Antiquity to the Middle Ages in Cascia (Italy). In 2021, a second Conference, devoted to the same topic, was held at Le Mans University (France). The articles collected in this work constitute a selection of the oral presentations or posters presented during the two Conferences. In the first two sections of the book, the reader will find contributions ranging from different ways of understanding seismic phenomena to strategies of post-disaster management, adaptation and resilience employed by societies and political authorities. From the third part onwards, palaeoseimological and archaeological data (for the most part previously unpublished) are presented on various sites in the Italian peninsula and the wider Mediterranean world and its frontiers. The final section is devoted to the emerging field of multidisciplinary studies on the specific characteristics of reconstruction and post-seismic building techniques. As a whole, using a multidisciplinary approach, the contents of the book aim to push forward knowledge on human/environment relations in the longue durée, contribute to the protection of the architectural and cultural heritage, and promote a culture of risk management in territories exposed to potential seismic activity."